Interest and tax burden on corporations in the Czech industrial and banking sector after 2008 - Jaroslav Sedláček; Daniel Němec (Review of Economic Perspectives, 2018)
The present paper deals with the interest and tax burden of corporations in the Czech industrial and banking sector as well as with the identification of the differences between the two sectors, including the evaluation of their developmental trends in the period after the economic and financial crisis of 2008. The interest and tax burden on business entities is determined by negative cash flows that reduce the value of their assets and equity. The basis of the research is the analysis of both components of the financial burden on corporations in these sectors over the past eight years and the identification of factors influencing their capital structure and performance. According to DuPont's equation, the burden is expressed by interest and the tax reduction of corporation's earnings before interest and taxes. The amount of the financial burden depends on the macroeconomic environment where the corporations operate. Our analysis identified an asynchronous dependence between the real payments and changes in the interest and tax rates. The reduction of both rates has had a positive effect on the performance of Czech corporations and increased their capital resources. They became more attractive to foreign investors, and the return on invested capital improved. Based on the results of the analysis, we evaluated the differences in the performance of the average corporation in the banking and industrial sectors.
Keywords: 330; financial burden of corporations; tax burden; interest burden; accounting statements; financial analysis; performance and efficiency